Pengaruh Struktur Modal, Reputasi Auditor, Dan Keputusan Investasi Terhadap Opini Audit Pada Perusahaan Sektor Energi - Ricky Bryan D.P. Tampubolon; Alya Triana Putri Nasaru; Diva Alia Amelia; Keisha Ambar Hafidah; Zahra Nabila (CV. ITTC INDONESIA, 2025)
This study aims to determine the effect of capital structure, auditor reputation, and investment decisions on audit opinions in energy companies listed on the Indonesia Stock Exchange. This study was conducted because previous studies showed inconsistencies in explaining the factors that shape audit opinions, especially in high-risk sectors such as energy. This study uses a quantitative method with an associative approach. The data used is secondary data obtained from the financial statements and independent auditor reports of energy companies up to 2023. The data was analyzed using logistic regression. The uniqueness of this study lies in its focus on the energy sector, which has high volatility, as well as the simultaneous testing of three internal factors that may influence audit opinions. The results show that capital structure has a significant effect on audit opinions, auditor reputation has a positive and significant effect on audit opinions, while investment decisions do not show a significant effect. This study also finds that companies with higher leverage tend to receive more cautious audit opinions from auditors.